Embedding heritage awareness among school children through inquiry-based projects for outreach programmes - Md. Sharif, Harlina; Baniyamin, Nurhaya; Abdul Razak, Rajabi (2020)
This paper presents the experience of the Kulliyyah of Architecture and Environmental Design in teaching Conservation as a specialisation in the programme of Bachelor of Applied Arts and Design (B.AAD). In Malaysia, the awareness of conservation of cultural heritage is limited to only a certain sector of the society. A preliminary study on the level of awareness of young generation on the values of traditional built heritage reveals the lack of interest in the subject of history, as well as lack of awareness of the significance of traditional Malay built heritage. The main factor for this phenomena can be attributed to the lack of interesting reading sources. Most history books are wordy, bland and almost all are written for adults. In addition, a survey on the syllabus being taught in primary schools reveals that the subject of built heritage was never introduced to young children. Even at secondary school level the subject of traditional Malay architecture for example is not introduced. Based on a survey conducted among school teachers and interview with museum outreach programme personnel, two interactive projects were designed by final year students in the B.AAD programme. The first is a 3D pop-up book on the historical relationship between the Sultanate of Melaka and Admiral Zheng He (aka Cheng Ho, c. 1371- 1433 CE) who was a Chinese Muslim eunuch explorer sent by the Ming dynasty emperor Yongle (r. 1403-1424 CE) on seven diplomatic missions to increase trade and secure tribute from foreign powers. The second project is a 3D puzzle of a traditional Malay house kit with design elements of the house that can be assembled and disassembled. The projects aim to introduce interactive and fun educational kit that could be marketed as part of museum outreach programme or primary school syllabus. The incorporation of this inquiry-based and interactive learning mechanism in primary school children education may assist in embedding cultural heritage awareness and recognition of the significance of traditional Malay architecture which is soon diminishing.